MORFOMETRIK DAN GENETIKA PADA IKAN Pterocaesio chrysozona DI PASAR IKAN MODERN MUARA BARU, DKI JAKARTA - Mohd Adip Setiawan; Hawis Maduppa (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTCoral fish is one of the biota that live in coral reef ecosystems and its life is very dependent on thecondition of coral reefs. Pterocaesio chrysozona is a species of reef fish from the family Caesionidae that live in groups around coral reefs between 0-25 meters deep. Morphogenetic, morphological and DNA barcoding based measurements have advantages in identifying species that have been proven successful in identifying reef fish species. Morphometric and morphological analysis results showed that the overall specimens identified were Pterocasio chrysozona fish. It is directly proportional to the DNA Barcoding analysis which is read at the level of Pterocasio chrysozona fish species with a percentage of 93% Query Cover and Per. Ident 96.54%.Keywords: Reef fish, Pterocaesio chrysozona, morphometrics, morphology, DNA barcoding.ABSTRAKIkan karang adalah salah satu biota yang hidup pada ekosistem terumbu karang dan hidupnya sangat bergantung pada kondisi terumbu karang. Pterocaesio chrysozona merupakan spesies ikan karang dari Famili Caesionidae yang hidup bergerombol di sekitar terumbu karang kedalaman antara 0-25 meter. Pengukuran yang berbasis morfogenetik, morfologi dan DNA Barcoding memiliki kelebihan dalam melakukan identifikasi spesies yang terbukti berhasil dalam melakukan identifikasi spesies ikan karang. Hasil analisis morfometrik dan morfologi menunjukkan secara keseluruhan spesimen yang teridentifikasi adalah ikan Pterocasio chrysozona. Berbanding lurus dengan analisis DNA Barcoding yang terbaca pada tingkat spesies ikan Pterocasio chrysozona dengan persentase Query Cover 93% dan Per. Ident 96,54%.Kata kunci : ikan karang, Pterocaesio chrysozona , morfometrik, morfologi, DNA barcoding